Using Body Language to Make and Maintain a Solid First Impression and to Decode Students’ Behaviours - Özlem Köprülü (Sakarya University Journal of Education)
In daily life people use their body language subconciously and effectively. Some research findings have suggested that two thirds of communication and at least 75% of all classroom communication is nonverbal. Therefore, body language makes a great difference in helping teachers to make and maintain a solid first impression in a classroom full of curious students. This study tries to explain various body movements, gestures and facial expressions that could help teachers to leave a good impression on students and to decode students’ behaviours correctly and behave accordingly. In order to learn students’ ideas about how various gestures and body language affect them in the lesson, a questionnaire including six pictures and multiple choice questions were conducted on 53 randomly chosen 3rd class students who are attending English Language Teaching Department at Buca Faculty of Education at Dokuz Eylul University and results were used to help teachers.